ANALISIS PEMAHAMAN PESERTA DIDIK PADA KONSEP LOGARITMA BERDASARKAN TEORI APOS DI MAN 2 PONTIANAK - Irwandi Irwandi; Zubaidah Zubaidah; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractMany students have difficulty in understanding the topic of the logarithm. The difficulties learners in understanding the logarithm can be anticipated by understanding how learners build logarithmic concept in their minds. The method of this research is qualitative, descriptive based on the theory of APOS. The results of this research show that on the learners with an understanding of the stages of action determines the value of the logarithm by means of guesses and limited to determining the value of the logarithm of the simple integer only. Learners with an understanding of the stages of the process can determine the logarithm of the number 1 as a result of action interiorisasi to guess. Learners with an understanding of the stage object has been able to sum, subtracting, dividing and multiplying the logarithm, but does not yet have an understanding of the whole of the definition of the logarithm. Learners with an understanding of the stages of the scheme can associate a logarithm with other concepts. Keywords:  Understanding, Concept of Logarithm, APOS Theory